Investment Commitments and the Number of New Projects Decline in East Asia and Pacific - Izaguirre, Ada Karina; Park, JangHo (World Bank, Washington, DC, 2012)
Private activity in infrastructure in East Asia and Pacific slowed in 2008, according to just-released data from the Private Participation in Infrastructure Project database. Both investment commitments and the number of new projects declined, in both the first and second half of the year. New energy projects and existing telecommunications operators accounted for most the annual investment. The region attracted 10 percent of the year's total investment commitments in developing countries. In 2008, 78 infrastructure projects with private participation reached financial or contractual closure in 10 low- or middle-income countries of East Asia and Pacific. These projects involve investment commitments (hereafter, investment) of US$8.6 billion. Infrastructure projects implemented in previous years had additional commitments of US$6.8 billion, bringing total investment in 2008 to US$15.4 billion.